Revisiting the Fantasy–Reality Distinction: Children as Naïve Skeptics. Issue 5 (15th March 2013) - Woolley, Jacqueline D.; E. Ghossainy, Maliki
Abstract : Far from being the uncritical believers young children have been portrayed as, children often exhibit skepticism toward the reality status of novel entities and events. This article reviews research on children's reality status judgments, testimony use, understanding of possibility, and religious cognition. When viewed from this new perspective it becomes apparent that when assessing reality status, children are as likely to doubt as they are to believe. It is suggested that immature metacognitive abilities are at the root of children's skepticism, specifically that an insufficient ability to evaluate the scope and relevance of one's knowledge leads to an overreliance on it in evaluating reality status. With development comes increasing ability to utilize a wider range of sources to inform reality status judgments.